Evaluation of Instructor Capability: Perspective from Building Information Modeling Competition Students in Mainland China - Pengcheng Pan; Maoyuan Li; Chenshuo Li; Xuemeng Zong (Buildings)
Building information modelling (BIM) technology, which has experienced rapid development, has become the focus of digital education learning in architecture, engineering, and construction (AEC) related disciplines. However, BIM education is still confronted with the disconnection between theoretical education and engineering practice. In mainland China, BIM competitions are an important digital platform for higher education practice teaching. As the organizer and leader of student participants, BIM instructors, especially their BIM capability, have an important impact on digital education. Previous research on BIM capability did not involve the field of BIM education, and the existing BIM capability framework is not entirely applicable to evaluating the BIM capability of instructors. Semi-structured interviews based on grounded theory (GT) and structural equation modeling (SEM) were used to construct a five-dimensional model containing 23 capability indicators. The research findings highlighted the multi-dimensional nature of BIM capability for instructors and indicated that personnel capability was the most important for instructors, while process capability was considered the most dispensable. This is significantly different from the emphasis on technical and process capability in BIM capability research in the traditional AEC industry. It was also found that students from different levels of universities and different educational backgrounds had different demands for the BIM capability of instructors. The results of this study will help universities select excellent instructors, improve the quality of BIM education in universities, and cultivate more outstanding BIM talents for the development of BIM in the AEC industry, thereby promoting the digital practice of BIM education in universities.